1963
DOI: 10.1128/jb.86.3.517-526.1963
|View full text |Cite
|
Sign up to set email alerts
|

Specific Viral Interference in Hela Cell Cultures Chronically Infected With Coxsackie B5 Virus

Abstract: HeLa cell cultures chronically infected with Coxsackie B5 virus. J. Bacteriol. 86:517-526. 1963.-The presence of large amounts of Coxsackie B5 virus in culture fluids of a HeLa subline, serially propagated over a 3-year period, provided evidence for attainment of a viral carrier state. Human serum in the growth medium of carrier cultures appeared prerequisite for maintenance of a stable virus-cell equilibrium. Virus was eliminated from HeLa cells by addition of B5 antiserum to the growth medium, whereas subcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1966
1966
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…The absence of interference to superinfection of rubella-infected cell strains with echovirus 11 confirms the finding of Goffe (42). Variability in resistance to superinfection of carrier cultures with related and unrelated viruses has been noted by others (43,45,46). Crowell (46) found specific resistance to related enteroviruses and this resistance was found to be an adsorption defect, which was not demonstrated to be the case in our rubella-infected cells.…”
Section: Discussionsupporting
confidence: 87%
“…The absence of interference to superinfection of rubella-infected cell strains with echovirus 11 confirms the finding of Goffe (42). Variability in resistance to superinfection of carrier cultures with related and unrelated viruses has been noted by others (43,45,46). Crowell (46) found specific resistance to related enteroviruses and this resistance was found to be an adsorption defect, which was not demonstrated to be the case in our rubella-infected cells.…”
Section: Discussionsupporting
confidence: 87%
“…The finding that the monoclonal antibody Rmc CB3-CB3RD blocked receptors for some picornaviruses outside of the specific receptor family (i.e., E6 and coxsackievirus A21) was unexpected (6,8). In addition, the monoclonal antibody blocked attachment to RD cells of CB1-RD, CB3-RD, and CB5-RD variant viruses, which presumably use the same receptor site on HeLa and RD cells as well as a second site on HeLa cells.…”
Section: Discussionmentioning
confidence: 97%
“…These monoclonal antibodies include the one for receptors on HeLa cells for CB1, CB5, and CB6 obtained by Campbell and Cords (5), one for the receptor on HeLa, RD, and monkey kidney cells for the three poliovirus immunotypes obtained by Minor et al (30), one for receptors on HeLa cells for the major group of HRVs found by Colonno et al (5a), and the one reported herein, which has an extended receptor specificity to completely block receptors for CB1, CB3, CB5, E6, and coxsackievirus A21 on HeLa cells and CB1-RD, CB3-RD, and CB5-RD on RD cells. In general these monoclonal antibodies help to confirm the existence of separate receptor families for the different species of picornaviruses, which first were recognized by virus competition experiments (1,3,6,7,14,23,29,32,34).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Eclipsing of Adenovirus in Presence of Its Satellite.--In order to determine the event during the adenovirus replication cycle at which the satellite exerts its interfering effect, experiments were performed to determine if satellite virus interfered with adenovirus adsorption, penetration, or eclipse. The first two of these steps have been shown to be the sites of interference in other virus systems (18,19). In order to test viral eclipsing, it is important that cells be infected simultaneously.…”
Section: Quantitation Of a Denovirusmentioning
confidence: 99%